2021
DOI: 10.9734/ajfar/2021/v11i430208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stocking Density on Growth Performance of Labeo bata in Cage at River Padma, Rajshahi, Bangladesh

Abstract: As a result of climate change, aquaculturists are seeking adaptive culture techniques for sustainable aquaculture. In this case, cage culture is a suitable technique that can mitigate the challenge of climate change, but due to the lack of knowledge of proper stocking density, often productions are not satisfactory. Therefore, the experiment was conducted to evaluate the influence of stocking density on growth and production of an endangered minor carp bata (Labeo bata) in cages for a period of 120 days in Pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The maximum value was recorded with the T 1 in the fourth months. Samad et al (2021) suggested the temperature in the culture setup were 28.50°C among the treatments while Nahar et al (2021) found temperature fluctuated between 25.01 and 26.13°C; on the other hand Shajib et al (2018) showed the temperature could be ranged between 25.25 and 27.50 °C in hapa set up was found to be suitable for fish growth, as better weight gain and lower FCR were recorded during this period. The amount of dissolved oxygen in water is another key water quality characteristic that fish rely on to survive (Makori et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The maximum value was recorded with the T 1 in the fourth months. Samad et al (2021) suggested the temperature in the culture setup were 28.50°C among the treatments while Nahar et al (2021) found temperature fluctuated between 25.01 and 26.13°C; on the other hand Shajib et al (2018) showed the temperature could be ranged between 25.25 and 27.50 °C in hapa set up was found to be suitable for fish growth, as better weight gain and lower FCR were recorded during this period. The amount of dissolved oxygen in water is another key water quality characteristic that fish rely on to survive (Makori et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…In the winter month the oxygen content of the aquaculture pond were less than in the summer months. Samad et al (2021) suggested the dissolved oxygen (DO) level in cage culture might be fluctuated between 5.48 ± 0.02 and 5.72 ± 0.11 mg/l; while the average DO level ranged between 5.02±0.45 and 5.27±0.60 mg/l in small catfish aquaculture pond reported by Nahar et al (2021). On the other hand a poly culture setup suggested that the DO might fluctuated between 5.29±0.27 and 5.93±0.66 mg/l (Zafar et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation